Rescuing Democracy in the Age of the Internet. Issue 3 (8th September 2015) - Runciman, David
Abstract : Throughout almost the entire history of democracy—from pre-Socratic Greece up to the second half of the twentieth century—its champions faced little difficulty in identifying its enemies. Critics of democracy consistently lined up to attack it on ideological and philosophical grounds. The litany of complaints was familiar: Democracy is an ignorant, unreliable, unstable form of rule; putting power in the hands of the people entrusts decision-making to those who are incapable of making the right decisions, either because of their natural incapacity or because social arrangements have denuded them of their ability to know what they are doing; democratic politicians pander to the masses, and the masses reward them for it; democracies choose short-term gratification over long-term solutions and eventually pay the price. These charges were invariably accompanied by the promise of something better, the assumption being that almost any alternative regime would be an improvement on the inadequacies of democracy.